Kilka uwag o odważniku z domniemanym znakiem runicznym znalezionej na Górze Chełmskiej w Koszalinie. - Jankowski, Andrzej (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2013)
The paper reinterprets the chronology of a weight found in 1961 on Góra (Mount) Chełmska in Koszalin and a symbol placed on one of its poles. The symbol was believed by some scholars to be a runic sign. A re-analysis of the find has revealed that the weight is not an early medieval artefact and the sign is not a rune but a municipal mark.